Helicobacter Pylori infection in rheumatic and autoimmune diseases - Al Ghamdi, Khalid Mohammed; Aljohani, Khalid Mohammed; Almuawi, Saud Sayyaf; Alharbi, Mohanad Sulaiman; Alwabisi, Yazeed Hamdan; Albalawi, Yazeed Ahmed; Alrazouqi, Sarah Sayed; Almaghrabi, Sultan Khalil; Alshahrani, Arwa Eid; Almohi, Bushra Abdullah; Alshammari, Tamam Zamil; Bawareth, Rozana Louai (International Journal Of Community Medicine And Public Health, 2022)
Helicobacter pylori (H. pylori) infection is responsible for affecting almost 50% to 80% of people worldwide thus making it quite a prevalent bacterial infection. The relationship between infection and autoimmune disease have grown more obvious over the past 20 years. Although the exact cause of autoimmune diseases is unknown, it has long been hypothesized that genetically susceptible individuals may be more likely to develop autoimmune processes as a result of exposure to specific environmental agents, such as bacterial and viral infections or chemical exposures. One important factor in the development of autoimmune disorders is H. pylori infection. Clinically, H. pylori infection is frequently linked to peptic ulcer disease, while many infected people exhibit no symptoms. Atrophic gastritis, immunological thrombocytopenic purpura, and mucosa associated lymphoid tissue lymphoma are just a few of the illnesses that immune dysregulation has been linked to and reduced by H. pylori. Rheumatoid arthritis, systemic lupus erythematosus, and Sjogren's syndrome are examples of autoimmune diseases caused by an immune system that is malfunctioning in the body and invading healthy tissues. The purpose of this research is to review the available information about H. pylori infection in rheumatic and autoimmune disease. Numerous researchers have proposed that H. pylori may have a role in the emergence of autoimmune diseases due to its frequency and capability to alter human immune function. Although the results from majority of the present study findings in literature are contrasting. Further clinical research is needed to elaborately explain the association between autoimmune diseases and H. pylori infection.